Affirmative Pedagogies. Living and coexisting in a disadvantadged neighborhood (The case of Semi) - Cortés-González, Pablo (My University, 2013)
In this presentation I consider findings and methodological issues generated by a research called THE WINK OF THE POWER, THE SMILE OF THE CHANGE. Pedagogical study of resilience identity in situations of social, cultural and legal disadvantaged. The study draws upon narrative life history methods to understand the social experience of disadvantage and change
Keywords: Pedagogía; Justice; School; Resilience; Social exclusion; Narrative